2020
DOI: 10.1155/2020/7958041
|View full text |Cite
|
Sign up to set email alerts
|

Iron Chelation Properties of Green Tea Epigallocatechin‐3‐Gallate (EGCG) in Colorectal Cancer Cells: Analysis on Tfr/Fth Regulations and Molecular Docking

Abstract: In many studies, green tea epigallocatechin-3-gallate (EGCG) has already shown its therapeutic effects in colorectal cancer cells (CRC). However, its mechanism of actions in CRC is poorly elucidated. Hence, this study attempts to elucidate the mechanism of actions of green tea ECGG via iron chelation activity in CRC. In order to investigate this property, HT-29 cell lines (CRC) were treated with EGCG for 24 h, 48 h, and 72 h. From western blot analysis, EGCG had upregulated transferrin receptor (TfR) protein a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(11 citation statements)
references
References 41 publications
0
11
0
Order By: Relevance
“…One of the reasons for this could be that Iron (Fe) is a transition metal that forms chelates and complexes with phenolic plant secondary metabolites. It has been observed that epigallocatechin gallate acts as a robust Iron chelator (Md Nesran et al 2020 ). In our case, iron supplementation in the form of Fe-ZnO-NPs might have triggered the production of enhanced quantities of this compound to reduce the toxic effects of Iron and Zinc given in excess amounts (250 µg/ml).…”
Section: Resultsmentioning
confidence: 99%
“…One of the reasons for this could be that Iron (Fe) is a transition metal that forms chelates and complexes with phenolic plant secondary metabolites. It has been observed that epigallocatechin gallate acts as a robust Iron chelator (Md Nesran et al 2020 ). In our case, iron supplementation in the form of Fe-ZnO-NPs might have triggered the production of enhanced quantities of this compound to reduce the toxic effects of Iron and Zinc given in excess amounts (250 µg/ml).…”
Section: Resultsmentioning
confidence: 99%
“…One of the reasons for this could be the fact that Iron (Fe) is a transition metal that forms chelates and complexes with phenolic plant secondary metabolites. It has been observed that epigallocatechin gallate acts as a robust Iron chelator (Md Nesran et al, 2020). In our case, the supplementation of iron in the form of Fe-ZnO-NPs might have triggered the production of enhanced quantities of this compound to reduce the toxic effects of Iron and Zinc given in excess amounts (250 µg/ml).…”
Section: Hplc Analysis Of Fe-zno-nps Based Elicited Culturesmentioning
confidence: 67%
“…EGCG has been proven to protect pancreatic β cells against iron toxicity and erastin-induced ferroptosis through neutralizing iron and preventing GPX4 inactivation ( Kose et al, 2019 ). Moreover, EGCG can also act as an iron chelator to regulate the TFRC/FTH expression and to prevent GPX4 activation, resulting in the inhibition of ferroptosis ( Md Nesran et al, 2020 ). In addition to its antioxidative properties, EGCG is evidenced by clinical experience as an anticancer agent that modulates GPX4 levels to promote ferroptosis ( Zhu et al, 2017 ).…”
Section: Pharmacological Approaches To Ferroptosis Modulationmentioning
confidence: 99%